Tren Publikasi Tentang Ekonomi Hijau Dalam Perspektif Syariah : Sebuah Analisis Bibliometrik - Malihah, Lola; Mahfuza, Annisa; Habibah, Nur (Brida Provinsi Jambi, 2025)
Current economic activities often utilize natural resources without prudent consideration for environmental preservation efforts. Hence, the concept of green economy is crucial for national economic development. This aligns with Sharia principles, particularly in promoting societal well-being. There is a need to develop approaches that integrate environmental factors and ecosystems into economic paradigms, enabling government economic policies to integrate with environmental conservation efforts. Comprehensive literature on green economy research from a Sharia perspective is necessary to provide further insights into its development. This research aims to understand the progress, topical trends, and future directions of green economy research within the Sharia perspective. The study employs a quantitative descriptive research method with a bibliometric approach. Data consists of secondary data gathered from publication metadata on Google Scholar from 2015 to 2023, analyzed using Publish or Perish version 8.2.3944 and Vosviewer version 1.6.20. The findings indicate positive growth with 73 scholarly works on green economy from a Sharia perspective between 2015 and 2023. Frequently discussed topics include green economy, sustainable development, and Indonesia in relation to green economy from a Sharia perspective. Further in-depth and specific research is essential for the development of green economy topics within the Sharia perspective, particularly focusing on societal well-being, Islamic economics, natural resources, economic growth, and the environment.